2005
DOI: 10.1084/jem.20041538
|View full text |Cite
|
Sign up to set email alerts
|

NFATc2 and NFATc3 transcription factors play a crucial role in suppression of CD4+ T lymphocytes by CD4+ CD25+ regulatory T cells

Abstract: The phenotype of NFATc2−/− c3−/− (double knockout [DKO]) mice implies a disturbed regulation of T cell responses, evidenced by massive lymphadenopathy, splenomegaly, and autoaggressive phenomena. The population of CD4+ CD25+ T cells from DKO mice lacks regulatory capacity, except a small subpopulation that highly expresses glucocorticoid-induced tumor necrosis factor receptor family–related gene (GITR) and CD25. However, neither wild-type nor DKO CD4+ CD25+ regulatory T cells (T reg cells) are able to suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 27 publications
3
120
0
2
Order By: Relevance
“…This small TCR derived Ca 2+ response is significantly enhanced in the absence of CD5 suggesting that TCR generates better signals in T reg cells in the absence of CD5 and thus may contribute to their greater effectiveness. A role for calcium elevation in T reg function is supported by the finding that NFAT transcription factor is important for T reg cell function (41). There are reports suggesting that an interaction between NFAT and Foxp3 is required for the effector function of T reg cells (42)(43)(44)(45).…”
Section: Discussionsupporting
confidence: 49%
“…This small TCR derived Ca 2+ response is significantly enhanced in the absence of CD5 suggesting that TCR generates better signals in T reg cells in the absence of CD5 and thus may contribute to their greater effectiveness. A role for calcium elevation in T reg function is supported by the finding that NFAT transcription factor is important for T reg cell function (41). There are reports suggesting that an interaction between NFAT and Foxp3 is required for the effector function of T reg cells (42)(43)(44)(45).…”
Section: Discussionsupporting
confidence: 49%
“…In contrast to the established role of Ca 2+ , previous data revealed that nTreg in mice deficient for NFAT1 plus NFAT4 were neither decreased in number nor impaired in their suppressive capacity (14). Therefore, it was concluded that NFAT2 might be the important family member for controlling nTreg development and/or function (10).…”
mentioning
confidence: 77%
“…Therefore, NFAT/ICER complexes seem to be instrumental for the transcriptional attenuation of numerous NFAT-driven cytokine promoters in conventional CD4 + T cells. A critical role of NFAT factors for inhibitory complex formation is further strengthened by observations indicating that combined NFATc2/c3 deficiency rendered conventional CD4 + T cells unresponsive to suppression, although normal nTreg development was detected in those mice (11). Moreover, targeting ICER/ CREM in RNAi and antisense RNA approaches antagonized the nTreg-mediated suppression and/or inhibition of IL-2 production in conventional CD4 + T cells, rendering these effector T cells refractory to suppression (7,12).…”
mentioning
confidence: 86%